Factors related to the quality of life among ambulatory hypertensive patients in Asia: a systematic review - Winda Zulaiha Shahabudin,; Roszita Ibrahim,; Norfazilah Ahmad,; Syahnaz Mohd Hashim,; Norasyikin A. Wahab,; Hanis Ahmad,; Siti Aishah Mohd Sanef, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Hypertension has emerged as an enormous public health concern in recent decades, exerting detrimental effects on global mortality, morbidity, and disability rates. It serves as a major risk factor for cardiovascular disease and significantly impacts the quality of life of affected individuals. Addressing various factors is crucial to improve patients' quality of life. The primary objective of this study is to explore the factors associated with a deterioration in the quality of life, as well as their impact on the ambulatory hypertensive population residing in Asia. The literatures were reviewed from three databases which were WOS, Scopus and PubMed. All published literatures were English articles with free access, published between the years 2014 and 2023, and conducted in the Asian region. The paper highlights various factors associated with a decreased quality of life. These factors include gender (specifically, being female), older age, limited social support, lower levels of education, and comorbidities leading to reduced financial resources. Additionally, inadequate health literacy, non-compliance with medication regimens, and insufficient understanding of the disease are also linked to a diminished quality of life. Family and social support play pivotal roles in enhancing the quality of life for individuals with hypertension. Healthcare providers should prioritize the promotion of health literacy and encourage medication adherence to mitigate further complications related to hypertension.